MODIFIKASI KARBON AKTIF DARI CANGKANG JENGKOL DENGAN TiO2 UNTUK FOTODEGRADASI RHODAMIN B - Sari, Widya Rachmah; Hindryawati, Noor; Subagyono, R.R Dirgarini Julia Nurlianti (JURNAL ATOMIK, 2019)
Modifying activated carbon from jengkol shells with TiO 2 to degrade Rhodamine by UV irradiation has been done. Modification of KA-TiO 2 photocatalyst using the impregnation method. The photodegradation test of dyes was carried out with several parameters such as the variation of KA-TiO 2 catalyst weight and contact time. Photocatalyst characterization using X-ray diffraction (XRD), while for dye concentration using UV-Vis spectrophotometry. Difractogram XRD shows that the activated carbon material after modification with TiO 2 metal is characterized by the emergence of typical TiO 2 peaks. The results showed that the highest percentage of Rhodamine B degraded by KA-TiO 2 was 94.11% with a contact time of 120 minutes and a catalyst weight of 1.5 grams.